The Hypocephalus. - Mekis, Tamás (Archaeopress Egyptology Ser., 2020)
The hypocephalus is an element of Late Period and Ptolemaic funerary equipment--an amuletic disc placed under the head of mummies. Its shape emulates the sun's disc, and its form is planar (although it is occasionally concave). This volume analyses the written records and iconography of these objects.